Umiejętności kierownicze w procesie utrwalania kluczowych kompetencji przedsiębiorstw - Roszyk-Kowalska, Gabriela (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The set of core competencies of the enterprise formulated and implemented in a proper way distinguishes the particular company among its competitors. The phase of strengthening core competencies requires the particular level of essential management capabilities. Research conducted indicates that there is a gap between indispensable capabilities and capabilities that managers possess in practice. The research result also show that there is no significant statistic relation between the evaluation of manager's capabilities and the gender, age, experience, level in the hierarchy that particular employee occupies, sector, character (features) of goods and services that company provides or income level. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 142-147